Managing Coal Enterprise Competitiveness in the Context of Global Challenges - Ahmad Kultur Hia; Nurdelima Waruwu; Aan Komariah; Dedy Achmad Kurniady; Herlan Suherlan; Inna Rykova; Konstantin Ordov; Izabella Elyakova; Elena Romanenko; Mikhail E. Kosov (Emerging Science Journal, 2023)
Increased geopolitical tensions and economic sanctions imposed by the U.S., the European Union, and other countries against Russian sectors of the economy have caused a slowdown of economic growth in Russia and significantly restricted access to international capital markets, creating many problems for coal enterprises due to the rapid growth of competition. Russian and Indonesian coal companies need to adopt coping strategies and implement effective management practices to successfully counter the various global challenges facing the coal sector. The article aims to develop coal enterprise competitiveness management in the context of global challenges in 2022, as exemplified by Russia and Indonesia, considering the main role of these two countries in global coal exports. The management process was empirically assessed, and a comprehensive qualitative focus group session was conducted to achieve this goal. Fifty-five top managers of Russian and Indonesian coal companies participated in the focus group session to collect data for identifying all the factors and indicators to be accounted for in a holistic assessment of the companies’ competitiveness. Suggestions were worked out for the development of coal companies in Russia and Indonesia, regarding current changes, to increase their competitiveness. Doi: 10.28991/ESJ-2023-07-02-021 Full Text: PDF